Mitochondrial dysfunction and metabolic reprogramming in acute kidney injury: mechanisms, therapeutic advances, and clinical challenges - Cao, Meiling; Zhao, Xueqi; Xia, Fang; Shi, Mingyue; Zhao, Danyang; Li, Lei; Jiang, Hongkun (Frontiers in Physiology, 2025)
Acute kidney injury (AKI) is a clinical syndrome associated with considerable morbidity and mortality. Despite therapeutic advancements, renal recovery and long-term outcomes remain suboptimal. Understanding the pathogenesis of AKI and identifying strategies to prevent its progression have become critical global health priorities. Mitochondrial dysfunction and changes in cellular energy metabolism play key roles in the pathophysiology of AKI. In patients with AKI, proximal tubular cells (PTCs) commonly exhibit impaired mitochondrial biogenesis, characterized by dysregulated mitochondrial dynamics, reduced fusion, and increased fission. Additionally, autophagy dysfunction may occur, contributing to compromised fatty acid β-oxidation (FAO) and subsequent energy deficits. To resolve this energy crisis, under the regulation of multiple signaling pathways, including AMP-activated protein kinase, mechanistic target of rapamycin complex 1, sirtuins, peroxisome proliferator-activated receptor alpha, peroxisome proliferator-activated receptor-γ coactivator 1α, and hypoxia-inducible factor-1 alpha, surviving PTCs may undergo a temporary shift toward glycolysis-dominant energy metabolism. This adaptive metabolic reprogramming is frequently associated with the activation of the pentose phosphate pathway and the suppression of gluconeogenesis. However, a sustained impairment of fatty acid oxidation (FAO) and continued reliance on glycolysis can result in the accumulation of lipids and glycolytic intermediates. This, in turn, may trigger inflammatory responses, promote epithelial-mesenchymal transition, impair tubular repair mechanisms, and contribute to the development of renal fibrosis. Collectively, these pathological processes facilitate the progression from acute kidney injury (AKI) to chronic kidney disease (CKD). Although interventions aimed at enhancing mitochondrial biogenesis, restoring mitochondrial and FAO homeostasis, and employing remote ischemic preconditioning have demonstrated potential in mitigating AKI progression, further investigation is required to address unresolved concerns related to their safety and clinical efficacy.